Analysis Effect of Butyrate Addition on Butanol Production by PVA-Immobilized Clostridium acetobutylicum ATCC 824 in Batch Culture Fermentation - Atika Nandini; Wei-Yu Chou; Dilirani Nagarajan; Jo-Shu Chang (Future Science)
The cultivation of PVA-immobilized Clostridium acetobutylicum ATCC 824 in CRM medium including 60 g/L of glucose as a carbon source was used to produce butanol. The addition of various butyrate concentrations was analyzed to stimulate metabolic pathways toward butanol production. Anaerobic incubation conditions were maintained at a temperature of 37°C for 24-36 h. The A-B-E batch fermentation was performed at the optimum condition as follows: temperature of 37°C, the glucose concentration of 60 g/L, and pH of 4.5 (controlled). The highest butanol production of 14.94 g/L was achieved with butyrare addition of 2.5 g/L, and the highest butanol yield of 0.61 mol butanol/mol glucose was achieved at the addition of 5 g/L. The experimental result showed that butanol production and yield increase when the addition of butyrare is less than 5 g/L. Despite that, with further higher butyrare concentration, butanol production decreases accompanied by decreased glucose consumption. The lowest butanol production of 11.74 g/L was obtained at the addition of 7.5 g/L butyrare.